2018
DOI: 10.1101/467605
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reevaluation of the Role of ERK3 in Perinatal Survival and Post-Natal Growth Using New Genetically-Engineered Mouse Models

Abstract: 38The physiological functions of the atypical MAP kinase ERK3 remain poorly characterized. 39Previous analysis of mice with a targeted insertion of the lacZ reporter in the Mapk6 locus 40 (Mapk6 lacZ ) showed that inactivation of ERK3 in Mapk6 lacZ mice leads to perinatal lethality 41 associated with intrauterine growth restriction, defective lung maturation, and neuromuscular 42 anomalies. To further explore the role of ERK3 in physiology and disease, we generated novel 43 mouse models expressing a catalytica… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 22 publications
(27 reference statements)
2
4
0
Order By: Relevance
“…The physiological roles of the atypical MAP kinase ERK3 remain to be fully investigated. Recently, we reported that ERK3-deficient mice or mice expressing a catalytically-inactive allele of ERK3 show a reduced growth rate postnatally (Soulez et al, 2019). A similar growth retardation phenotype was described in another mouse model of ERK3 deficiency (Ronkina et al, 2019).…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…The physiological roles of the atypical MAP kinase ERK3 remain to be fully investigated. Recently, we reported that ERK3-deficient mice or mice expressing a catalytically-inactive allele of ERK3 show a reduced growth rate postnatally (Soulez et al, 2019). A similar growth retardation phenotype was described in another mouse model of ERK3 deficiency (Ronkina et al, 2019).…”
Section: Discussionsupporting
confidence: 60%
“…We have shown previously that mice expressing a kinase-dead (KD) allele of ERK3 (Mapk6 KD/KD ) have a reduced postnatal growth rate as compared to WT control mice (Soulez et al, 2019). This growth phenotype affected both female and male mice.…”
Section: Defective Postnatal Skeletal Muscle Growth In Mice Expressin...mentioning
confidence: 99%
See 3 more Smart Citations